In-plane phase transition of an integral membrane protein: nucleation of the OmpF matrix porin rectangular polymorph. - Dorset, D L (1989)
A hexagonal polymorph (a = 79 A) of OmpF matrix porin from Escherichia coli spontaneously transforms to a rectangular form (a = 79 A, b = 137 A) after several months' storage in the refrigerator. Nucleation of this second polymorph is first disclosed by diffuse streaks in electron diffraction patterns or in computer-generated Fourier transforms of electron microscope images. With time, this streaking is resolved as an apparent superlattice, and eventually domains of orthorhombic polymorph are detected in the parent hexagonal lattice that can be oriented in either of three directions, depending on the polarity of the orthorhombic crystal growth. Models for this phenomenon based on protein trimer rotation successfully explain the progress of the phase transition and, if protein-protein interactions are the most important interactions between adjacent trimers in the lipid matrix, the transition is quite similar to what occurs with molecular crystals.